Pengembangan Media Kartu "Juragan Kuliner Nusantara" untuk Meningkatkan Minat P5 Kewirausahaan Siswa SD - Kamaliah, Aulan Nisa Ulil; Prasetyo, Abdul Rahman (Jurnal Pendidikan dan Penciptaan Seni, 2025)
In creating learning media, innovation is needed to create an effective and interesting learning environment. Fun learning innovations enable students to be more actively involved and gain meaningful experiences. This research aims to analyze the needs for P5 entrepreneurship learning in elementary schools, develop card game-based learning media as a solution, and test its impact on students' entrepreneurial interest. This research uses the ADDIE development method (Analyze, Design, Development, Implementation, and Evaluate). The expert validation results showed that the material feasibility was 90.8% (Very Feasible category) and the media feasibility was 78.1% (Decent category). The N-gain calculation of 0.75 indicates an increase in students' entrepreneurial interest in the High category. Apart from that, field observations in December 2024 recorded the suitability of the cards and rulebook for the game "Juragan Culinary Archipelago" at 94.4% (Very Feasible category). The percentage of student interest in the game reached 89.25%, categorized as Very Interesting. These findings indicate that the card game "Juragan Kuliner Nusantara" is not only interesting and worth using, but also has the potential to increase students' interest in entrepreneurship. The implication of this research is that card game-based learning media can be widely applied to support entrepreneurship learning in elementary schools.